Stability convection in a couple stress fluid saturated in an anisotropic porous medium with internal heating effect - Mohd Rusdi, Nadia Diana; Mohd Mokhtar, Nor Fadzillah; Senu, Norazak; Mohamed Isa, Siti Suzilliana Putri (Semarak Ilmu Publishing, 2020)
Internal heating effect with stability convection in a couple stress fluid saturated in an anisotropic porous medium has been studied numerically using linear stability analysis. The presence of internal heating on couple stress fluid in an anisotropic porous medium heated from below has been verified. The momentum equation and Boussinesq approximation is used for the density variation in the porous medium. By using Chebyshev Tau method numerically, the eigenvalue problems of the perturbed state were obtained from a normal mode analysis. The effect of the Rayleigh number, internal heat source and anisotropy parameter has been shown graphically. The critical Rayleigh number also has been obtained and plotted on the system. From the result, it is found that the mechanical anisotropy parameter and internal heating effect destabilized the system while couple stress fluid and thermal anisotropy parameter help in stabilizing the system.